A more-Comers populAtion trEated with an ultrathin struts polimer-free Sirolimus stent: an Italian post-maRketing study (the CAESAR registry) - Tarantini, Giuseppe; Cardaioli, Francesco; De Iaco, Giuseppe; Tuccillo, Bernardino; De Angelis, Maria Carmen; Mauro, Ciro; Boccalatte, Marco; Trivisonno, Antonio; Ribichini, Flavio; Vadalà, Giuseppe; Caramanno, Giuseppe; Caruso, Marco; et al. (Frontiers in Cardiovascular Medicine, 2024)
The use of contemporary drug-eluting stents (DES) has significantly improved outcomes of patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI). However, concerns exist regarding the long-term pro-inflammatory effects of durable polymer coatings used in most DES, potentially leading to long-term adverse events. First generation polymer-free stent technologies, such as sirolimus and probucol-eluting stents (PF-SES), have shown an excellent safety and efficacy profile. Aim of this study was to evaluate the safety and efficacy of the new ultrathin Coroflex ISAR NEO PF-SES, in a more-comers PCI population.The CAESAR (A more-Comers populAtion trEated with an ultra-thin struts polimerfree Sirolimus stent: An Italian post-maRketing study) registry is a multicenter, prospective study conducted in Italy, enrolling more-comers CAD patients undergoing PCI with the Coroflex ISAR NEO stent. Patients with left main (LM) disease, cardiogenic shock (CS) or severely reduced leftventricular ejection fraction (LVEF) were excluded. The primary endpoint was target-lesion revascularization (TLR) at 1 year.Results: A total of 425 patients were enrolled at 13 centers (mean age 66.9±11.6 years, Diabetes mellitus 29%, acute coronary syndrome 67%, chronic total occlusion 9%). Of these, 40.9% had multi-vessel disease (MVD) and in 3.3% cases, the target lesion was in-stent restenosis (ISR).Clinical device success was reached in 422 (99.6%) cases. At one year, only 2 (0.5%) subjects presented ischemia-driven TLR. The 1-year rates of TVR and MACE were 0.5% and 5.1% respectively. Major bleeding was observed in 4 (1.0%) patients.In this multicenter, prospective registry, the use of new ultrathin Coroflex ISAR NEO PF-SES in a more-comers PCI population showed good safety and efficacy at 1-year.